The Effectiveness Of Soy Milk Extension On The Influence And Protein Consumption For Pregnant Women 4t - Megawati Megawati; Eka Agustina; Jennifer Angely Dwytomi Putri; Khoirunnisa Khoirunnisa (CV. AFDIFAL MAJU BERKAH, 2026)
Stunting is a chronic nutritional problem that may begin during pregnancy and is strongly influenced by maternal nutritional status, particularly adequate protein intake. Pregnant women with 4T risk factors (too young, too old, short birth spacing, and high parity) are more vulnerable to nutritional problems that can affect fetal growth. This community service activity aims to improve the knowledge and skills of high-risk pregnant women in fulfilling protein intake through nutrition education and training on soy milk (PUSUI) preparation as an alternative source of plant-based protein. A quasi-experimental design without a control group was applied using a participatory educational approach. The activity was conducted in Tanjung Gunung Village, Central Bangka Regency, involving 25 pregnant women with 4T risk factors. The intervention consisted of interactive educational sessions, discussions, and hands-on demonstrations and practice in soy milk preparation. Evaluation was carried out descriptively through observation and post-test assessments to measure participants' understanding. The results showed an improvement in participants' knowledge regarding the role of protein during pregnancy and their ability to independently prepare soy milk. In addition, participants demonstrated good acceptance of soy milk as an alternative protein source. In conclusion, this community service program is effective and feasible as a supportive strategy to increase protein intake among high-risk pregnant women and contribute to stunting prevention from the prenatal period.